2012
DOI: 10.1007/s10238-012-0178-5
|View full text |Cite
|
Sign up to set email alerts
|

Kidney post-transplant monitoring of urinary glycosaminoglycans/proteoglycans and monokine induced by IFN-γ (MIG)

Abstract: Allograft rejection during the first year after renal transplantation can lead to persistent allograft dysfunction and reduced long-term graft survival. Thus, it is important to define early predictors of kidney damage, less invasive than allograft biopsy. Urinary glycosaminoglycan/proteoglycan concentration and distribution, N-acetyl-β-(D)-glucosaminidase (NAG), and monokine induced by IFN-γ (MIG) levels were evaluated in the immediate post-transplant and during a 1-year follow-up. We observed increased urina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Early and ongoing activation of inflammatory immune cell responses, also termed innate or acute cellular rejection, are reported to induce ongoing organ damage and to be a significant driving force for late chronic transplant vasculitis, rejection and graft loss 36 – 44 . Late organ damage is also known to be caused by recurrent antibody-mediated immune rejection.…”
Section: Discussionmentioning
confidence: 99%
“…Early and ongoing activation of inflammatory immune cell responses, also termed innate or acute cellular rejection, are reported to induce ongoing organ damage and to be a significant driving force for late chronic transplant vasculitis, rejection and graft loss 36 – 44 . Late organ damage is also known to be caused by recurrent antibody-mediated immune rejection.…”
Section: Discussionmentioning
confidence: 99%
“…UTI purification is performed by two steps. The first one exploits the high negative charge density of the O ‐linked CS to capture this small PG, by anion exchange chromatography . The second one allows resolving the protein moiety, according to its molecular weight, by SDS‐PAGE.…”
Section: Discussionmentioning
confidence: 99%
“…According to a plethora of papers, bikunin can be considered a positive acute phase protein . Over the past few years we have described variations of UTI/glycosaminoglycans (GAGs) levels in some pathological conditions such as chronic glomerulonephritis , type 1 diabetes , kidney transplantation , and systemic lupus erythematosus , as well as during the physiological menstrual cycle in fertile women . Recently, we have reported that UTI may represent a useful marker for monitoring renal function in Fabry's disease .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In urine, GAGs consist mainly of heparan sulfate (HS), CS, and, in negligible quantity, dermatan sulfate [6]. In the general population, bikunin has been reported to occur at higher levels in various pathological conditions exhibiting chronic inflammation, including cancer [11], chronic glomerulonephritis [12, 13], kidney transplantation [14], type 1 diabetes [15], and systemic lupus erythematosus [16]. Moreover, we reported variations of urine bikunin levels during the physiological menstrual cycle in fertile women [17].…”
Section: Introductionmentioning
confidence: 99%